Literary Orientalism: Main Contours Up to the British Romantic Period - Kidwai, A R (KnE Social Sciences, 2018)
Literary Orientalism assumed the status of a new, fascinating subfield of English literary studies in 1980s, after the publication of Edward Said’s influential work, Orientalism (1978). However, earlier critical studies too, pointed to the varied perception of the other, including the Orient/ Orientals in English literary works down the millennia. The paper under study traces out the genesis of this tradition from 12